Dimensionamiento de la capacidad del generador eléctrico y montaje en la Universidad Técnica de Cotopaxi La Maná - Herrera Alvarado, José Ignacio (2013)
The present project was developed in the area framed backup power, giving solution to power shortages of Technical University of Cotopaxi La Maná, which occurred when the power outages took place in the city, the main objective of this project was to study the installed load to size the capacity of the electric generator, and the generator was installed with the purpose of supplying the demand for energy in the University.